Mode of Birth Influences Preterm Infant Intestinal Colonization With Bacteroides Over the Early Neonatal Period. (December 2015) - Gregory, Katherine E.; LaPlante, Rose D.; Shan, Gururaj; Kumar, Deepak Vijaya; Gregas, Matt
Abstract : Background: Intestinal colonization during infancy is important to short- and long-term health outcomes. Bacteroides, an early member of the intestinal microbiome, is necessary for breaking down complex molecules within the intestine and function to assist the body's immune system in fighting against potentially harmful pathogens. Little is known about the colonization pattern of Bacteroides in preterm infants during the early neonatal period. Purpose: This study measured Bacteroides colonization during the early neonatal period in a population of preterm infants, based on clinical factors including mode of birth, antibiotics, and nutrition. Methods: Bacterial DNA was isolated from 144 fecal samples from 29 preterm infants and analyzed using quantitative real-time polymerase chain reaction. Analyses included liner mixed models to determine which clinical factors affect Bacteroides colonization of the infant gut. Results: We found that infants born via vaginal canal had a higher rate of increase in Bacteroides than infants born via cesarean section ( P < .001). We did not find significant associations between antibiotic administration and differences in nutritional exposures with Bacteroides colonization. Implications for Practice: These findings highlight the significant influence of mode of birth on Bacteroides colonization. While mode of birth is not always modifiable, these study findings may help develop interventions for preterm infants born via cesarean section aimed at overcoming delayed Bacteroides colonization. Implications for Research: Greater study of the intestinal microbiome and the clinical factors relevant to the preterm infant is needed so that interventions may be developed and tested, resulting in optimal microbial and immune health.